Retail Mix Dan Kepuasan Konsumen Minimarket - Siti Maryama; Yayat Sujatna (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2018)
The purpose of this study is to (1) analyzing the level of retail mix consumer satisfaction; (2) analyze the dominant variable in retail mix consumer satisfaction; (3) analyze the difference of retail mix consumer satisfaction performed. The observed of the retail industry is Alfamidi and Indomaret. The study was designed into a descriptive-quantitative method. The source of primary data obtained from the questionnaire of 100 respondents. The formulating variable of retail mix includes: merchandise assortments, pricing, customer services Store design and display, communication mix, and location. Data analyze by using descriptive, analysis of factors, and t-test. The result confirmed that the level of retail mix consumer satisfaction in both industry is relatively similar. However, it can be stated that the respondents were more satisfied to Indomaret compared with Alfamart.